Artificially designed membranes using phosphonated multiwall carbon nanotube-polybenzimidazole composites for polymer electrolyte fuel cells - Kannan, Ramaiyan; Aher, Pradnya P.; Palaniselvam, Thangavelu; Kurungot, Sreekumar; Kharul, Ulhas K.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry Letters, 2010)
The ability of phosphonated carbon nanotubes to offer an unprecedented approach to tune both proton-conductivity and mechanical stability of hybrid polymer electrolytes based on the polybenzimidazole membrane is demonstrated for fuel cell applications. The covalent attachment between the amino group of the 2-aminoethylphosphonic acid precursor and CNTs has been confirmed by NMR and IR experiments, while EDAX analysis indicates that one out of every 20 carbon atoms is in the CNT is functionalized. Proton conductivity of the composite membrane shows a remarkable 50% improvement in performance while a maximum power density of 780 and 600 mW cm(-2) is obtained for the composite and pristine membranes, respectively. Finally, the ultimate strength determined for the composite and pristine membranes is 100 and 65 MPa, respectively, demonstrating the superiority of the composite. This study opens up a new strategy to systematically tune the properties of polymer electrolytes for special applications by using appropriately functionalized CNTS.

Facile construction of non-precious iron nitride-doped carbon nanofibers as cathode electrocatalysts for proton exchange membrane fuel cells - Palaniselvam, Thangavelu; Kannan, Ramaiyan; Kurungot, Sreekumar (Chemical Communications, 2011)
We demonstrate a facile construction of iron nitride-doped carbon nanofiber by effectively utilizing the existing slit pores and rough edges along the inner wall of the substrate as originated by virtue of its cup-stack structure for effectively increasing the number of active sites and consequently the oxygen reduction activity.

Activity modulated low platium content oxygen reduction electrocatalysts prepared by inducing nano-order dislocations on carbon nanofiber through N-2-doping - Palaniselvam, Thangavelu; Irshad, Ahamed; Unni, Bipinlal; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2012)
We demonstrate how surface unsaturation developed during small order buckling of graphene interlayer upon doping iron nitride (i.e., FeNx) moieties in carbon nanofiber can be utilized as a very efficient mode of surface activation to establish fine distribution of Pt nanoparticles with 10 wt %. The surface dislocations have been effectively modulating the oxygen reduction characteristics of Pt through synergistic effects of the interacting species. The simultaneous enhancement of dispersion of Pt and oxygen reduction reaction (ORR) activity with a low weight percentage of dispersed Pt has been attained by FeNx doping, which increases the density of the active sites owing to the formation of fine and abundant delaminated regions on the CNF surface. HR-TEM images clearly depict the fine distribution of Pt nanoparticles on the delaminated regions of FeNxCNF. The stable incorporation of Pt on nitrogen doped active sites has been further confirmed by observing the formation of Pt-N peak at 391.5 eV using XPS analysis. The fine distribution of Pt nanoparticles along the abundant nanopockets between the buckled graphene layers helped the system to attain significantly high electrochemically active surface area of Pt as evident from the cyclic voltammetric studies. The mass activity of PtFeNxCNF at 0.9 V vs RHE is 4.9 mA mgPt(-1) which is two times higher than that of E-TEK. The superior catalytic activity (exchange current density (i(0)) at 0.8 V is 2.61X 10(-6)) could be further confirmed by single cell evaluation of the membrane electrode assembly (MEA) of polymer electrolyte fuel cell (PEFC), where the cathode electrode was fabricated from this new catalyst.

Efficient oxygen reduction electrocatalyst from graphene by simultaneously generating pores and nitrogen doped active sites - Palaniselvam, Thangavelu; Aiyappa, Harshitha Barike; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
A simple way to simultaneously create pores and nitrogen doped active sites on graphene for the electrochemical oxygen reduction reaction (ORR) is developed. The key aspect of the process is the in-situ generation of Fe2O3 nanoparticles and their concomitant dispersion on graphene by pyrolyzing graphene oxide (GO) with the iron phenanthroline complex. Thus the deposited Fe2O3 nanoparticles act as the seeds for pore generation by etching the carbon layer along the graphene-Fe2O3 interface. Detection of the presence of Fe3C along with Fe2O3 confirms carbon spill-over from graphene as a plausible step involved in the pore engraving process. Since the process offers a good control on the size and dispersion of the Fe2O3 nanoparticles, the pore size and distribution also could be managed very effectively in this process. As the phenanthroline complex decomposes and gives Fe2O3 nanoparticles and subsequently the pores on graphene, the unsaturated carbons along the pore openings simultaneously capture nitrogen of the phenanthroline complex and provide very efficient active sites for ORR under alkaline conditions. The degree of nitrogen doping and hence the ORR activity could be further improved by subjecting the porous material for a second round of nitrogen doping using iron-free phenanthroline. This porous graphene enriched with the N-doped active sites effectively reduces oxygen molecule through a 3e(-) pathway, suggesting a preferential shift towards the more favourable 4e(-) route compared to the 2e(-) reaction as reported for many N-doped carbon nano-morphologies. The 90 mV onset potential difference for oxygen reduction as compared to the state-of-the art 20 wt% Pt/C catalyst is significantly low compared to the overpotentials in the range of 120-200 mV reported in the literature for few N-doped graphenes.

Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

Nanoporous graphene by quantum dots removal from graphene and its conversion to a potential oxygen reduction electrocatalyst via nitrogen doping - Palaniselvam, Thangavelu; Valappil, Manila Ozhukil; Illathvalappil, Rajith; Kurungot, Sreekumar (Energy & Environmental Science, 2014)
A simple way to produce an efficient metal-free oxygen reduction electrocatalyst from graphene by generating nanopores in the matrix and subsequently establishing nitrogen-doped active sites along the pore openings is demonstrated. Well-structured nanoporous graphene (pGr) and photoluminescent graphene quantum dots (GQDs) could be simultaneously generated by a chemically assisted oxidative treatment of graphene. The process helped to knock out small pieces of Gr through epoxide formation, which subsequently resulted in the generation of GQD and pGr simultaneously. A longer oxidation time increased the quantity of GQDs and also resulted in a higher photoluminescent (PL) quantum yield. The PL quantum yield of GQD formed after 72 h of the oxidative treatment (GQD-72) was 15.8%, which is greater than the previous reported values. The TEM images showed matching sizes for GQDs and the pores present in pGr, implying that the pores are generated by the removal of GQDs from graphene during the oxidative treatment. Since pore openings are expected to give higher levels of unsaturation and defect sites in the system and are thus being treated as fertile regions for heteroatom doping, pGr-72 was further subjected to nitrogen (NpGr-72). NpGr-72 displayed excellent activity towards the electrochemical oxygen reduction reaction (ORR) compared to nitrogen-doped non-porous graphene (NGr) and many other reported nitrogen-doped carbon materials. A distinct 50 mV gain in the overpotential and 2.5 times increment in the kinetic current density (j(k)) have been achieved in the case of NpGr-72 compared to NGr. Interestingly, unlike NGr, NpGr-72 effectively reduced the oxygen molecule with a greater involvement of the preferred four-electron pathway. Additionally, the overpotential difference of NpGr-72 with respect to 20 wt% Pt/C is only 60 mV. Additionally, in a single cell evaluation under anion exchange membrane fuel cell (AEMFC) conditions, NpGr-72 exhibited a maximum power density of 27 mW cm(-2), which is significantly higher than the corresponding value of 10 mW cm(-2) obtained for NGr. Thus, the overall enhancement in the performance characteristics of NpGr-72 is attributed to the higher content of nitrogen (7.8 wt%) and its large proportion of desired chemical environment, which could be established by utilizing the high level of carbon unsaturation around the pore openings.

Nanoporous graphene enriched with Fe/Co-N active sites as a promising oxygen reduction electrocatalyst for anion exchange membrane fuel cells - Palaniselvam, Thangavelu; Kashyap, Varchaswal; Bhange, Siddeswar N.; Baek, Jong-Beom; Kurungot, Sreekumar (Advanced Functional Materials, 2016)
Here, a simple but efficient way is demonstrated for the preparation of nanoporous graphene enriched with Fe/Co-nitrogen-doped active sites (Fe/Co-NpGr) as a potential electrocatalyst for the electrochemical oxygen reduction reaction (ORR) applications. Once graphene is converted into porous graphene (pGr) by a controlled oxidative etching process, pGr can be converted into a potential electrocatalyst for ORR by utilizing the created edge sites of pGr for doping nitrogen and subsequently to utilize the doped nitrogens to build Fe/Co coordinated centers (Fe/Co-NpGr). The structural information elucidated using both XPS and TOF-SIMS study indicates the presence of coordination of the M-N (M = Fe and Co)-doped carbon active sites. Creation of this bimetallic coordination assisted by the nitrogen locked at the pore openings is found to be helping the system to substantially reduce the overpotential for ORR. A 30 mV difference in the overpotential () with respect to the standard Pt/C catalyst and high retention in half wave potential after 10 000 cycles in ORR can be attained. A single cell of an anion exchange membrane fuel cell (AEMFC) by using Fe/Co-NpGr as the cathode delivers a maximum power density of approximate to 35 mWcm(-2) compared to 60 mWcm(-2) displayed by the Pt-based system.
Keywords: electrocatalyst; nitrogen doping; oxygen reduction reaction; porous grapheme; quantum dots